Study of economic risks when implementing innovation project - Хавер, Вікторія Миколаївна (Technology audit and production reserves, 2013)
The article suggests systematic approaches to assess and manage economic risks when implementing an innovative project. On the basis of selected innovative projects, we studied the distribution of investment according to the stages of implementation of an innovative project, and built the scale of distribution of financial investment based on the assessment of each stage of implementation of an innovation process. Using the methods of statistical data processing, we have calculated the average values and statistical parameters of the distribution of the total funding according to the stages of the innovation process. To study the willingness of investors to invest in a project with a certain degree of risk and the effectiveness of capital investment, we have conducted a questionnaire surveys of investors of small and medium-size rnterprises. Based on these results, using the statistical software method of data processing we obtained results in the form of empirical dependences.